Effect of Lower Limb Compression Stockings on Hemodynamic Stability in Obstetric Patients undergoing Lower Segment Cesarean Section under Spinal Anaesthesia - Ali, Iftikhar; Iftikhar, Hina; Rahman, Habib Ur; Majeed, kaukab; khalid, Usman; Latif, Hira (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare the effects of lower limb compression stockings and control in terms of frequency of bradycardia, hypotension and hypotensive symptoms in a group of obstetric patients undergoing lower segment cesarean section under spinal anaesthesia. Study Design: Quasi-experimental study. Place and Duration of Study: Department of Anesthesiology Combined Military Hospital, Multan Pakistan, from Aug 2020 to Feb 2021. Methodology: One hundred women undergoing cesarean section under spinal anaesthesia from 18-45 years were included. Obstetric patients between 18–45 years of age, Non-labouring parturient, ASA Status I / II planned for Caesarean section were included. Patients were randomly divided into two treatment groups, i.e., Mechanical pump Group (Group M) and the Control Group (Group C), with Consecutive Non-probability sampling. The frequency of hypotensive symptoms, hypotension and bradycardia in both groups was noted. Results: Frequency of hypotensive symptoms, hypotension and bradycardia in the compression stockings group was found in 18(36.0%), 8(16.0%) and 11(22.0%) patients while in 38(76.0%), 32(64.0%) and 30(60.0%) patients in the control group (p-value = 0.0001). Conclusion: We concluded that the frequency of hypotensive symptoms, hypotension and bradycardia is less after lower limb compression stockings given to obstetric patients undergoing lower-segment cesarean section under spinal anaesthesia.